NIR/blue light emission optimization of NaY1−(x+y)YbxF4:Tmy upconversion nanoparticles via Yb3+/Tm3+ dopant balancing. Issue 26 (7th February 2018) - Bagheri, Ali; Li, Zheye; Boyer, Cyrille; Lim, May
Abstract : A data driven approach provides better understanding of the role of dopant balancing in the upconversion process and presents an effective strategy to enhance the optical properties of upconversion nanoparticles. Abstract : The increased applications of lanthanide-doped upconversion nanoparticles (UCNPs) in areas such as biomedical imaging and therapy have raised the demand for high quality nanocrystals with strong and controllable luminescence intensity. Whilst several different approaches including core/shell arrangement, dye sensitization and plasmonic metallic nanostructures have been employed to improve the upconversion luminescence of UCNPs, they may be impractical for scale-up production and applications. Herein, a mathematical model that was developed using multivariate statistical analysis shows that the key to optimising the NIR and blue light emission of NaY1−( x + y ) Yb x F4 :Tm y UCNPs is dopant balancing, where the composition of both ytterbium (Yb 3+ ) sensitizer and thulium (Tm 3+ ) activator is controlled in a way that the concentration and proximity of the dopants to each other can reduce cross-relaxation between Tm 3+ and self-quenching that is due to sub-optimal Yb 3+ concentrations, and consequently, favours efficient energy transfer between the Yb 3+ sensitizers and Tm 3+ activators. The data driven approach gives better understanding of the role of dopant balancing in the upconversion process and presents a general yet effective strategy to enhance the optical properties of UCNPs by manipulating the relative concentrations of the lanthanide dopants. This systematic approach will have important implications and it can be integrated with other emission enhancing strategies to produce high quality UCNPs for diverse applications in photonics, imaging, sensing, drug delivery and solar energy conversion.